Morfologi dan Pertumbuhan Planlet Hasil Induksi Poliploidi melalui Perlakuan Kolkisin pada Kuncup Bunga Anggrek Bulan (Phalaenopsis amabilis (L.) Blume) - Azmi, Tubagus Kiki Kawakibi; Sukma, Dewi; Aziz, Sandra Arifin; Syukur, dan Muhamad (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
Induction of polyploid gametes is one of useful plant polyploidization methods. Some of its benefits are to obtain triploid and tetraploid progenies at the same time by cross and self pollination. Previous research showed that some morphological characters which could be the indications of polyploidy plantlets before the analysis of chromosome number. Colchicine treatment on flower bud of diploid Phalaenopsis amabilis was conducted to determine the effect of colchicine on flower bud development, plantlets morphology and growth, and potential of polyploidy induction based on plantlets morphology. Colchicine concentrations in the experiment were 0, 50, 500, 1,000, and 2,000 mg L-1, with three days duration of treatments with aluminium foil wraps on flower buds. The results showed that high colchicine concentrations (2,000 mg L-1) inhibited flowers blooming of treated flower buds. Based on morphological characters, plantlets were classified into normal and putative polyploid plantlets. Putative polyploid plantlets from colchicine with the concentration of 50, 500, and 1,000 mg L-1 were 71.2, 86.4, and 100.0% respectively.Keywords: colchicine concentration, morphological characters, normal plantlets, putative polyploidy, reproductive organ